TRANSFORMASI PEMBIAYAAN KESEHATAN DALAM PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DI ERA DIGITAL - Sofia Rahma Ujung; Ismi Larasati Hasibuan, Rahmadani Sagala, Fitriani Pramita Gurning (Jurnal Kesehatan, 2024)
One crucial aspect of human existence is the health sector. What's more, technology will never stop developing. Due to the convergence of digital, biological and physical systems, the health sector is the party most likely to benefit from Industry 4.0, but may also be the party least prepared. The aim of this research is to determine the financing received by the community from the JKN program in this era. digital, whether the program provides adequate health protection, and whether this program really causes an increase in welfare for society as a whole. The method used is to analyze articles published in the last 5 years through Google Scholar searches. The results of this research are that to achieve various important goals of health development in a country, such as equitable access to health care and quality services, strong, stable and sustainable health financing is very important. for health development. In the current digital era, the JKN financing and health service system is running well and the system used is getting easier and speeding up the verification process in administration.